Infiltração microbiana em remanescentes de obturação de canais radiculares acrescidos de selador temporário - Paes, Fabio Resende (2006)
This study aimed to determine coronal leakage of root canals filling remnants when employing Sealapex , used or don t used temporary restorative materials Cotosol or Super Bonder, by means of differents microbial indicators. Thus, 32 single-rooted human teeth were used, which were shaped until the file size 50 and assigned to 4 groups. A group was used as control. In the study model, a platform was employed, which was split in two halves: an upper chamber where the microbial suspension containing the biological indicators was introduced (E. faecalis + S. aureus + P. aeruginosa + B. subtilis + C. albicans); and a lower chamber containing the culture medium Brain Heart Infusion, in which 3mm of the apical region of teeth were kept immersed. Interpretations of the time to occur microbial leakage were made daily for 60 days, using the turbidity of the culture medium which is indicative of microbial contamination, as a reference. The data obtained were submitted to the Kruskal-Wallis test. The results show that in the three: Group 1 - remaining obturation with Sealapex of 5mm; Group 2 - remaining obturation with Sealapex of 5mm and plug of 1mm Cotosol; Group 3 - remaining obturation with Sealapex of 5mm and plug of 1mm Super Bonder; didn t show statistical significant difference (p<0.05). In the group 1 didn t finding microbial leakage in 100% of the samples and for groups 2 and 3 in 87,5%.